A capillary electrophoresis method for the determination of soluble monosaccharides in Ginkgo biloba leaves. Issue 2 (28th November 2021) - Liu, Shuo; Li, Xin; Yang, Xifeng; Zhou, Linhui; Liang, Xiangfeng; Qiu, Ruchen; Fa, Yun
Abstract: A method for the simultaneous determination of six monosaccharides by pre‐column derivatization with 1‐phenyl‐3‐methyl‐5‐pyrazolone and capillary electrophoresis was developed in this work. The derivatization (i.e., reaction temperature, capillary electrophoresis duration, and extraction number) and separation (i.e., pH and buffer concentration) conditions for capillary electrophoresis were optimized. Results showed that the limits of detection under optimal conditions were in the range of 0.036–0.35 mg/L with a mean correlation coefficient >0.99. The recoveries were in the range of 87.3–108.49%, and the relative standard deviations of intra‐ and inter‐day variations were in the ranges of 2.2–3.8 and 3.2–5.0%, respectively. The method was successfully applied to the analysis of six free monosaccharides in three types of Ginkgo biloba leaves.